Communication Network on Social Capital Relations of Salt Production Workers - Imam Sofyan; Moch. Imron Rosyidi; R. Bambang Moertijoso (Komunikator, 2023)
Statistically, the production of people’s salt is still the most abundant national-scale salt production in Indonesia. Madura Island, the largest salt-producing island in Indonesia, also contributes the largest labor force in Indonesia. This shows that the potential for workers in Madura is still very significant. Therefore, this research aims to see the communication network of salt production workers in Madura. This study uses a descriptive quantitative method with a communication network analysis approach. The study shows that the mapping of social capital relations in people’s salt production can be seen from three relationships: bonding, bridging, and linking. In bonding relations, where the internal labor is still dominated by a few people, the hubs or links in the sociogram are seen to be centered on only one point. Meanwhile, the bridging relation is evenly distributed. This shows the opportunity for workers to strengthen their bias capacity with a demonstration plot mechanism and learn from others in need outside their community. Moreover, in the linking relationship, there is a wide gap in the community.